Utilization of a Continuous External Tissue Expansion System to Assist in Primary Closure of a Large Anterolateral Thigh Donor Site Defect - Andrew G. Silver; Richard C. Baynosa (Case Reports in Surgery)
Primary closure of a large anterolateral thigh (ALT) flap donor site defect with the assistance of an external tissue expansion system is presented. The dimensions of this donor site (12 cm × 40 cm) and its percentage of leg circumference (34%) would make this site likely to require skin grafting or further flap coverage based on the results of previously published literature.